Pro‐inflammatory cytokines favor the emergence of ETV6‐RUNX1‐positive pre‐leukemic cells in a model of mesenchymal niche. (2nd March 2020) - Beneforti, Linda; Dander, Erica; Bresolin, Silvia; Bueno, Clara; Acunzo, Denise; Bertagna, Mayla; Ford, Anthony; Gentner, Bernhard; Kronnie, Geertruy te; Vergani, Patrizia; Menéndez, Pablo; Biondi, Andrea; et al.
Summary: ETV6‐RUNX1 (E/R) fusion gene, arising in utero from translocation t(12;21)(p13:q22), is the most frequent alteration in childhood acute lymphoblastic leukemia (ALL). However, E/R is insufficient to cause overt leukemia since it generates a clinically silent pre‐leukemic clone which persists in the bone marrow but fails to out‐compete normal progenitors. Conversely, pre‐leukemic cells show increased susceptibility to transformation following additional genetic insults. Infections/inflammation are the most accredited triggers for mutations accumulation and leukemic transformation in E/R + pre‐leukemic cells. However, precisely how E/R and inflammation interact in promoting leukemia is still poorly understood. Here we demonstrate that IL6/TNFα/ILβ pro‐inflammatory cytokines cooperate with BM‐MSC in promoting the emergence of E/R + Ba/F3 over their normal counterparts by differentially affecting their proliferation and survival. Moreover, IL6/TNFα/ILβ‐stimulated BM‐MSC strongly attract E/R + Ba/F3 in a CXCR2‐dependent manner. Interestingly, E/R‐expressing human CD34 + IL7R + progenitors, a putative population for leukemia initiation during development, were preserved in the presence of BM‐MSC and IL6/TNFα/ILβ compared to their normal counterparts. Finally, the extent of DNA damage increases within the inflamed niche in both control and E/R‐expressing Ba/F3, potentially leading to transformation in the apoptosis‐resistant pre‐leukemic clone. Overall, our data provide new mechanistic insights into childhood ALL pathogenesis.